Traditional Portuguese Lullabies: what do they sing about? (Música Hodie, 2012)
This research project was developed at Instituto de Estudos da Criança1 (University of Minho, Braga, Portugal) in 2008 and 2009. It focused on promoting Portuguese traditional music as a privileged field for educational practice. Considering the scarcity of good quality published Portuguese musical repertoire for musical activities in pre-school, the project started with the collection and recovery of traditional Portuguese lullabies in old song books and libraries across the country; musical activities based on the musical concepts found in the lullabies were experimented in pre-school context and organized in didactic sequence. The lullabies’ lyrics were studied in order to identify recurrent themes and topics. Five main themes were found in the collection of studied lullabies. This article presents the conclusions of the project concerning the types of textual contents and themes found in the collected lullabies.Keywords: Early-childhood; Music education; Oral literature; Popular culture; Portuguese lullabies.